Analisis performa quality rate pada produk moorlife menggunakan metode six sigma dan kaizen serta statistical quality control - Bilqis, Delita; Pulansari, Farida (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT XYZ is a manufacturing company engaged in the plastic container packaging and printing industry, with a focus on high product quality. To maintain production quality, the company has a Quality Control (QC) department that is responsible for controlling and ensuring that the products produced meet the standards. However, the company often faces complaints from customers regarding product inconsistencies, such as inappropriate colors, flowlines, unmolded products  and black spots. Based on the analysis, it was found that the body travel square product has the  highest reject rate  , with a total of 2015 pcs rejects. The types of non-conformities that occurred included black spots (1047 pcs), non-standard colors (624 pcs), unmold (180 pcs), and flowline (164 pcs). To overcome this problem, analysis was carried out using Six Sigma method and Kaizen analysis, as well as Statistical Quality Control. The results of the analysis show that the average Six Sigma value is 3.22 with a minimum target of 3.4 or equivalent to 6 sigma and the average DPMO value is 66,126, indicating that the production quality is quite good.